The Effectiveness Of Using Google Form Examination Questions In Ict Subjects Class VIII - Yuliana, Yuliana; Ramdhani, Lisda; Rahmawan, Ardi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine the effectiveness of using Google Forms in even semester exam questions. This research uses a descriptive method with a quantitative approach. The research subjects were 23 students. simple random sampling technique. Data analysis techniques are 1) reduction; 2) presentation; and 3) conclusion The results of this research concluded that the use of Google forms was proven to be effective in implementing the Even Semester Examination. The use of Google Form is easy to implement 78.3% of students, ease in answering questions, 91.3% of students agreeing, Google Form in terms of time is more flexible results of 91.3% of students, statement regarding It was fun answering exam questions using Google Form 86.9% of students agreeing. Through online exams using Google Form, I further improved my abilities, with 82.6% of students agreeing. It is more effective during exams using Google Form compared to using paper, 91.3% of students agree, I am more satisfied during exams using Google Form, 91.3% of students agree, I prefer exams using paper, 47.8 % of students agree, using Google Form during exams is more time-saving, 95.6% of students agree the average being in the very good category